Modern Database Management Systems and Organizational Strategies (International Journal of Food and Nutritional Sciences, 2022)
In the contemporary digital landscape, organizations are increasingly reliant on sophisticateddatabase management systems (DBMS) to efficiently manage vast amounts of data. Thisresearch paper explores the role of modern database management systems in organizationalstrategies, emphasizing their significance in enhancing operational efficiency, decision-makingprocesses, and overall competitiveness